A MULTICRITERIA-BASED LOCATION OF AN INDUSTRIAL PARK IN A DEFINED AREA IN IPATINGA, MINAS GERAIS STATE, BRAZIL / Localização de um parque industrial em uma área definida em Ipatinga-MG utilizando a análise multicritério - Saulo Henrique de Faria Pereira; Maria Lúcia Calijuri; Sheila Cristina Martins Pereira; Nolan Ribeiro Bezerra; Maria de Nazaré Costa de Macedo (Sociedade & Natureza)
This paper aims to identify an area of over 5 ha for setting up an industrial park in Ipatinga microregionin Minas Gerais State, Brazil. Ipatinga is both nationally and internationally regarded as a model cityin terms of development because of Usiminas Company, which is one of the greatest metallurgic industrialpowers of Minas Gerais State. Setting up an industrial park in this framework is essential to attractpotential investors, to foster purchase of products manufactured by Usiminas, and thus to promotefiscal incentives to the municipality, which may contribute to Ipatinga socioeconomic development. Amulticriteria analysis was carried out, applying fuzzy logic (IDRISE software), ArcGis and imagesavailable from Google Earth and made a mosaic. Areas suitable for the industrial park implantationand the most suitable area were found by means of a cost-benefit analysis. Since hiring qualified laborafter setting the park up would eventually implicate migration of several people from other regions, adwelling study was also carry out. The results indicate that multicriteria analysis is an important toolfor decision-making throughout the process of assessing and selecting areas to set up striking enterprises.